Analysis of legislative acts in water management - J. Nesiba; R. Cuhlova (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This paper focuses on the development of Czech laws of water resource protection. The presented research examines the statistical data of the number and type of legislative acts concerning to water protection issued in the Czech Republic during the period 1990-2019. Several types of legislative acts are followed in administrative law and statistically compared by the development in time and its type. The survey focuses on general water protection acts, water sewage management, agriculture sector, hygiene standards, and the protection of the basins of Czech rivers (e.g., blue water and gray water). METHODS: The analysis firstly concerns to the development of the number of legislative acts during 1990-2019 and secondly discusses a diversification of the legislative acts types (laws, decrees, resolutions, regulations, and strategic plans). A total of 12,272 legislative acts is analyzed during three phases of Czech modern history: 1990-1992 (Czechoslovakia), 1993-2003 (Czech Republic before its accession to the European Union), and 2004-2019 (Czech Republic in the European Union). FINDINGS: Statistical elaboration of legislative acts proves that it is possible to determine different types of water management over time. Protection of water resource management in the Czech Republic was forming from crisis management (1990-1992), via operational management (1993-2003) to strategic management (2004-2019). Current trends after 2020 show a new trend towards integral management. CONCLUSION: Findings provide better understanding of changeable importance of water protection and management attitudes in the Czech Republic in reaction to the development of society.  ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================